Epidemiology and clinical features of coronavirus disease 2019 in children - Soo-Han Choi; Han Wool Kim; Ji-Man Kang; Dong Hyun Kim; Eun Young Cho (The Korean Pediatric Society, 2020)
Coronavirus disease-2019 (COVID-19), which started in Wuhan, China, in December 2019 and declared a worldwide pandemic on March 11, 2020, is a novel infectious disease that causes respiratory illness and death. Pediatric COVID-19 accounts for a small percentage of patients and is often milder than that in adults; however, it can progress to severe disease in some cases. Even neonates can suffer from COVID-19, and children may spread the disease in the community. This review summarizes what is currently known about COVID-19 in children and adolescents.